PENDEKATAN CTL BERBASIS PRAKTIKUM â€œMATERI LIMBAH CAIRâ€ DI SMK CBK PONTIANAK - Asradiah, Hayatun; Hairida, Hairida; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The aims of this research are to determine whether there are differences in learning outcomes between students who are taught by Contextual Teaching And Learning (CTL) practicum-based with students who are taught with conventional learning, and determine the influence of learning CTL practicum-based on liquid waste course toward learning outcomes of eleventh grade students of Cinta Bumi Khatulistiwa (CBK) Pontianak. The research method used is a quasi-experimental method, with a non equivalent control group design. The sample of this study was of eleven students of the SMK CBK Pontianak. Data collection tool in this study were a learning outcome test in the form of essays and interview guidelines. Based on data analysis using Mann Whitney U-test with = 5%, the Asymp.Sig (2-tailed) value was 0.047 <0.05 which indicates that there are differences in learning outcomes between students taught using the learning by CTL practicum-based with students who are taught with conventional learning on liquid waste course. The influence of CTL practicum-based learning has an effect of 34.61% on learning outcomes on liquid waste course of eleventh grade study of SMK CBK Pontianak. Keywords: Learning outcomes, liquid waste course, CTL practicum-based.